Rift Valley fever among children and adolescents in southwestern Saudi Arabia - Tarik A. Al Azraqi; Awad A. El Mekki; Ahmed A. Mahfouz (Journal of Infection and Public Health, 2013)
Summary: Purpose: Rift Valley fever (RVF) virus has expanded its geographical range, reaching Asia in 2000. This work investigated RVF seroprevalence among children born after the 2000–2001 outbreak in Saudi Arabia and compared it with the seroprevalence of adolescents born before the outbreak. Design: In a seroepidemiological study in southwestern Saudi Arabia (Jazan, Aseer, and Al-Qunfuda), a random sample of 389 children and adolescents was investigated. Data were collected regarding the subjects’ sociodemographic status, housing conditions, and animal contact. Blood samples were collected and tested for RVF-specific IgG and IgM. Results: None of the study samples were found to be seropositive for anti-RVF virus IgM. None of the study subjects aged 1–8 years (born after the outbreak) were positive for RVF-specific IgG. In contrast, 14 subjects (4.8%) aged 9–19 years (born before the outbreak) were positive for RVF-specific IgG. Among adolescents in our study, 4.9% were positive for anti-RVF IgG. This study showed that among adolescents, a history of contact with aborted animals (aOR = 13.361, 95% CI = 5.091–35.072) and transporting aborted animals (aOR = 18.861, 95% CI = 11.125–31.622) were significant risk factors. Conclusions: Despite the low virus activity recently reported among animals, neither clinically apparent RVF infections nor outbreaks among humans have been documented, indicating that the control measures taken by the Ministry of Agriculture and Ministry of Health are effective. Keywords: Infectious diseases, Epidemiology, Emerging diseases